The Influence of Health Education on Students' Knowledge Levels About theDangers of Consuming Sweet-Tasting Colored Drinks in Grades I, II, & III at SD Inpres 1 Nambaru, Parigi Moutong Regency - Andi Mariani; Badariati Badariati; Asmiwarty Abdullah; Hayati Palesa; Fauzan Fauzan (International Journal of Medicine and Health, 2026)
Sweetened beverages are drinks that contain high amounts of calories and sugar but provide little to no significant nutritional value. Limited public awareness, including among elementary school students, regarding the health risks associated with consuming sweet and artificially colored drinks may contribute to increased consumption habits. This behavior can raise the risk of various health problems, including obesity, type 2 diabetes mellitus, and kidney failure. This study aimed to determine the effect of health education on students’ knowledge regarding the dangers of consuming sweetened and colored beverages. This research employed a pre-experimental design using a one-group pretest-posttest approach. The study involved 90 respondents selected through the Total Sampling technique. Data were collected using a questionnaire and analyzed through univariate and bivariate methods using the Wilcoxon test. The results showed that before receiving health education, most respondents had a moderate to low level of knowledge. After the intervention, students’ knowledge improved significantly, with the majority achieving a good level of knowledge. Statistical analysis revealed a p-value of 0.000 (<0.05), indicating a significant effect of health education on students’ knowledge. Therefore, health education was found to be effective in increasing students’ understanding of the dangers of consuming sweetened and colored beverages.